Performance in folklore and the reclamation of indigenous knowledge systems through oral traditions - Viriri, Advice (2016)
The article investigates the relationship between orality and literacy with special reference to the changing cultural patterns of transmission of traditional folktales as a performing art. It go es on to explore how the performative effect is impacted upon by reducing them to written forms. Orality as indigenous knowledge, just like any historical inquiry, is a hallmark of hum an society. Folklore has, therefore, been ensuring that the transmission of African cultural values with all its historical sensitivities was in vogue since time immemorial. It addresses socio -political and psycho-cultural problems by virtue of their (folktales) didacticism . Folklore, in this article, will be broadly explained 'to include not only verbal art or orature, but also to encompass those fields impinging on folk culture, ethnology and mythology’ (Msimang 2002:11). Folktales are a product of culture and upholding the performative cultural heritage of a country is an important component of its people's national identity. The article argues that folktales should be given their rightful place as an embodiment of the performing arts to revive African cultural identity.